Enhanced thermal characterization of silica aerogels through molecular dynamics simulation - Yeo, Jing Jie (2016)
Porous structures of silica aerogels are generated using classical molecular dynamics, with the Tersoff potential, which has been re-parametrized for modeling silicon dioxides. This work demonstrates that this potential is superior to the widely used BKS potential in terms of characterizing the thermal conductivities of amorphous silica, by comparing the vibrational density of states with previous experimental studies. Aerogel samples of increasing densities are obtained through an expanding, heating and quenching process. Reverse non-equilibrium molecular dynamics is applied at each density to determine the thermal conductivity. A power-law fit of the results is found to accurately reflect the power-law variation found in experimental bulk aerogels. The results are also of the same order of magnitude as experimental bulk aerogels, but they are consistently higher. By analyzing the pore size distribution on different simulation length scales, we show that such a disparity is due to finite sizes of pores that can be represented, where increasing simulation length scales lead to an increase in the largest pore size that can be modeled.